Interference Analysis of PLC Convergence System - Ghyu Sun, Young; Min Hwang, Yu; Sim, Issac; Young Kim, Jin (International Journal of Engineering and Technology, 2018)
In this paper, we propose a convergence system with visible light communication (VLC) and powerline communication (PLC) for home network. Also, we analyze the performance of interference mitigation scheme for the proposedÂ Â  system model. The proposed system is able to offer multimedia services with high speed in indoor wireless environment. Interference scenario is suggested to demonstrate the proposed system. And the scenario analyzed by applying minimum mean square error (MMSE) and zero-forcing (ZF) schemes to reduce the interference. From simulation results, we confirm that interference has a significant effect on the proposed system performance and the applied detectors are highly effective for interference mitigation.